2014
DOI: 10.1002/chem.201403088
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Catalytic System for Asymmetric Copolymerization of Carbon Dioxide and Cyclohexene Oxide

Abstract: A new ligand can be easily prepared, and its intramolecular dinuclear zinc complexes act as a high performance catalyst for the asymmetric alternating copolymerization of cyclohexene oxide and CO2 under very mild conditions (1 atm CO2 , room temperature), affording completely alternating polycarbonates with up to 93.8 % enantiomeric excess (ee) and 98 % yield. A high Mn value of 28 600 and a relatively narrow polydispersity (Mw /Mn ratio) of 1.43 were also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…The same group also demonstrated the stereoselective alternating copolymerization of cyclohexene oxide and CO 2 with dimeric zinc complexes for the first time 25 . Besides, improved catalysts are still desirable to better control the properties of the resulting materials 26 . Similarly, many efforts are also devoted to designing catalysts able to promote the reaction of CO 2 with less-reactive oxiranes, which could also provide novel materials 27 .…”
Section: Box 1 | Coordination Modes Of Co 2 With Transition Metalsmentioning
confidence: 99%
“…The same group also demonstrated the stereoselective alternating copolymerization of cyclohexene oxide and CO 2 with dimeric zinc complexes for the first time 25 . Besides, improved catalysts are still desirable to better control the properties of the resulting materials 26 . Similarly, many efforts are also devoted to designing catalysts able to promote the reaction of CO 2 with less-reactive oxiranes, which could also provide novel materials 27 .…”
Section: Box 1 | Coordination Modes Of Co 2 With Transition Metalsmentioning
confidence: 99%
“…[143][144][145][146][147][148][149][150][151][152][153] Due to its stereoregularity, it is highly crystalline (although there is no clear trend between % crystallinity and % ee of the polymer) with a T m greater than atactic PCHC (though the reported melting values have varied greatly). [143][144][145][146] The only systematic study relating T m to % ee showed a positive correlation (T m = 234-267 °C) between the properties for samples ranging from 78-99% ee. 143 On the other hand, syndiotactic-enriched PCHC has been qualitatively described as 'amorphous' but no thermal data was reported.…”
Section: Degradable Polymersmentioning
confidence: 99%
“…This catalyst catalyzed the asymmetric alternating copolymerization of carbon dioxide and cyclohexene oxide in quantitative yield and high enantioselectivity of up to 93.8% ee. 19 This enantioselectivity was much better than that of Trost's dinuclear zinc−ProPhenol catalyst in the same reaction. 20 This activity is because of the relatively rigid ligand skeleton and appropriate chiral microenvironment provided by the four-membered heterocycle.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Although direct structural evidence for complex I could not be ascertained by electrospray mass spectral analysis or X-ray crystallography, previously similar work by Ding and coworkers suggests the formation of a dinuclear zinc ProPhenol complex, 20 and a dinuclear zinc−AzePhenol complex 2 could be captured by benzoic acid molecules recently reported by us. 19 Thus, we propose that the dinuclear zinc complex I is the real active catalyst species. The fact that N-benzylpyrrole (11b), N-benzoylpyrrole (11c), or N-methylpyrrole (11d) gives no reaction supports our guess.…”
Section: ■ Proposed Catalytic Mechanismmentioning
confidence: 99%